Public Speaking to Grow and Develop Speaking Skills in Elementary School Extracurricular Activities - Saada, Saron Aulia Himmatus; Sutama, S (Universitas Muhammadiyah Surakarta, 2023)
Purpose: This article aims to describe public speaking to develop speaking skills in linguistic aspects in elementary school extracurricular activities. Exploration public speaking to develop speaking skills in non linguistic aspects in elementary school extracurricular activities. Methodology: The research design used in this study is descriptive-qualitative and the research was conducted at Elementary School of Muhammadiyah Kottabarat Special Program Surakarta, Central Java, Indonesian. The subjects of the study were the teachers, trainers, and students who participated in public speaking extracurriculars. The data collection techniques included observation, interviews, and documentation, while the data analysis techniques used flow models. Results: The research results indicated that the students' speaking skills in the linguistic aspect were quite good, with upper-class students exhibiting superior language structure and word choice abilities compared to lower-class students. Additionally, the students' speaking skills in non-linguistic aspects had significantly increased due to their participation in extracurricular public speaking activities. Applications/Originality/Value: In elementary schools, public speaking skill have gaps that can be observed from how students tell stories or make speeches in front of the class. While some students are confident in public speaking, others lack confidence. In order to solve this challenge, the implementation of extracurricular activities that can effectively enhance the speaking skills of students is imperative. The current research delves into the discourse of students' speaking proficiency, particularly in the realm of Public Speaking extracurriculars. A dearth of studies exist on the topic of speaking abilities in extracurricular activities, making this research all the more significant.